The Effect of Preservatives in Cough Syrups on the Growth of Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Candida albicans - Kartikawati, Endah; Yus Hargono Cahyaning Yudi; Henny Setiawati; Syumillah (Pusat HKI, Paten, dan Publikasi Ilmiah Universitas Islam Negeri Raden Intan Lampung, 2026)
Generally, non-sterile pharmaceutical formulations contain preservatives added to protect the product from microbial growth. Preservatives are used in liquid non-sterile formulations, topical preparations, and other multi-dose forms. This study aims to assess the impact of preservatives in cough syrup on several microorganisms. The study utilized a cough syrup sample (Brand X) that was homogenized with phosphate buffer Solutions pH 7.2 and subsequently spiked with four types of microorganisms with six replicates: Pseudomonas aeruginosa ATCC 9027, Staphylococcus aureus ATCC 6538, Escherichia coli ATCC 8739, and Candida albicans ATCC 10231. Total plate count (TPC) method conducted and analyzed using one-way ANOVA with a 95% confidence level (α = 0.05), followed by post-hoc testing using SPSS 23 software. No growth of P. aeruginosa was observed in samples spiked with an initial concentration of 1.69 x 105 colonies/mL, indicating that the preservative in the cough syrup effectively inhibit P. aeruginosa. For E. coli and C. albicans, no significant difference in growth was observed compared to the initial concentration of microorganisms. S. aureus showed no significant decrease in logarithmic values, with the initial concentration of 1.88 x 105 colonies/mL reducing to 1.09 x 105 colonies/mL. The conclusion of this study is that the preservatives in cough syrup significantly reduce the growth of P. aeruginosa more effectively than S. aureus, E. coli, and C. albicans